1980
DOI: 10.2134/jeq1980.00472425000900030011x
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Sulfur in East Texas Lignitic Coal

Abstract: Distribution of sulfur and its three predominant forms in 10 lignitic coal seams developed in fluvial environments in east Texas was examined. The average sulfur content for individual seams varied from 0.88 to 3.98%, while the total sulfur content of 10‐cm sections of these seams varied from 0.53 to 16.79%. Sulfate sulfur was a minor component compared to pyritic or organic sulfur. The organic sulfur content determined by the standard American Society for Testing and Materials (ASTM) procedure as the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Acid production from carbonace6us materials has been recently documented in the Powder River Basin, Big Horn Basin, Hanna Basin and t.he Southwestern coal regions of Wyoming (Schnitzer and Fransway, 1982;Boon, 1984_a;Boon and Smith, 1985). Extremely acid mine soils, overburden and abandoned coal spoils have recently been identified ip New Mexico, Texas and Montana (Fisher and Munshower, 1984;Miller, et al, 1976;Arora, et al, 1980;Hagener, 1985). It should be mentioned that a wide range of textural materials.other than carbonaceous shales are capable of producing acidity in the 'western United States (Fisher and Munshower, 1984;Boon, 1984b;Boon and Smith, 1985).…”
Section: Acid Productionmentioning
confidence: 99%
“…Acid production from carbonace6us materials has been recently documented in the Powder River Basin, Big Horn Basin, Hanna Basin and t.he Southwestern coal regions of Wyoming (Schnitzer and Fransway, 1982;Boon, 1984_a;Boon and Smith, 1985). Extremely acid mine soils, overburden and abandoned coal spoils have recently been identified ip New Mexico, Texas and Montana (Fisher and Munshower, 1984;Miller, et al, 1976;Arora, et al, 1980;Hagener, 1985). It should be mentioned that a wide range of textural materials.other than carbonaceous shales are capable of producing acidity in the 'western United States (Fisher and Munshower, 1984;Boon, 1984b;Boon and Smith, 1985).…”
Section: Acid Productionmentioning
confidence: 99%
“…Acid production from carbonace6us materials has been recently documented in the Powder River Basin, Big Horn Basin, Hanna Basin and t.he Southwestern coal regions of Wyoming (Schnitzer and Fransway, 1982;Boon, 1984_a;Boon and Smith, 1985). Extremely acid mine soils, overburden and abandoned coal spoils have recently been identified ip New Mexico, Texas and Montana Proceedings America Society of Mining and Reclamation, 1985 pp 248-256 DOI: 10.21000/JASMR85010248 (Fisher and Munshower, 1984;Miller, et al, 1976;Arora, et al, 1980;Hagener, 1985). It should be mentioned that a wide range of textural materials.other than carbonaceous shales are capable of producing acidity in the 'western United States (Fisher and Munshower, 1984;Boon, 1984b;Boon and Smith, 1985).…”
Section: Acid Productionmentioning
confidence: 99%
“…• Hinkley, et al (1978) demonstrated that carbonaceous shales have higher pyrite concentrations than non-carbonaceous shales. Sulfide minerals occur in significantly higher poncentrations in the finer grained sedimentary rocks associated with coals: roof shales, .underclays and partings (Arora et al, 1980;Valkovic, 1983;Boon, 1984b) 0 Although pyrite is the dominant sulfide mineral in coal, significant amounts of other sulfide minerals have been identified: marcasite, sphalerite, galena, chalcopyrite and arsenopyrite (Finkelman, 1981;Valkovic, 1983). Dreher, et al (1985) recently identified galena, sphalerite, pyrite and chalcopyrite in Wyoming coal and overburden.…”
Section: Acid Productionmentioning
confidence: 99%